Heuristic and Hermeneutic Reading of 75 Kufic Towards Ramadan FOKS Indonesia: a Study in Riffaterre’s Semiotics - Adib Alfalah; Asep Sopian (Research Synergy Foundation, 2024)
In the current era of digital development, Muslim societies have unique and impactful ways of welcoming Ramadan; for instance,